Tower dungeon. 3 / Tsutomu Nihei ; tranlsation, Sam Malissa ; lettering, Darren Smith. - Nihei, Tsutomu, 1971- (Kodansha USA, 2025)
Level 25: Yuva and his companion fell into a trap set by deserters from the Royal Guard and face certain defeat. Their captors demand the adventurers are carrying a legendary relic called Dragonbane, and if they even knew what that was, it's still in doubt whether they could escape in order to rescue the princess!